Strategies Used in Translating the Harry Potter and the Sorcerer’s Stone Novel into Indonesian - Kurniawan, Adhitya; Setiawan, Alesandro Fritz; Esmara, Tania; Santoso, Wulandari (CV. Creative Tugu Pena, 2023)
The study was prompted by the necessity of using suitable translation strategies in the context of translating literary works. The study aimed to identify the translation strategies utilized in translating the Harry Potter and the Sorcerer’s Stone novel. The study utilized the qualitative research design to produce descriptive data. Furthermore, the thematic analysis was implemented in this study to categorize and analyze the data. In selecting the data, the researchers utilized the purposive sampling for data selection and selected the first, seventh, and eleventh chapters to be analyzed. The study resulted in the discovery that six out of the eight translation strategies proposed by Newmark were used (2003), namely the word-for-word, literal, faithful, semantic, free, and communicative translation strategies. Additionally, three of the translation strategies presented by Baker (2018) were employed to translate the idiomatic expressions in the novel. These strategies included the utilization of an idiom with similar meaning but different form, borrowing from the source language, and the omission of an entire idiom. This study further explored various existing theories regarding translation strategies and discovered connections between them. Furthermore, this study would be beneficial for translators, namely in deciding which translation strategies would be appropriate for specific situations. Keywords: Translation Strategies, Literary Translation, Idiomatic Translation